THE COMPARATIVE STUDY BETWEEN FLASHCARD AND SCRABBLE MEDIA TO MOTIVATE THE STUDENTS MASTERY IN VOCABULARY - Viklous, Belinda Ekharisti (JOEEL (Journal of English Education and Literature), 2022)
Mastering vocabulary is very important for EFL students.The purposes of thiscomparativestudy are to1) to determine thelevel of the studentsmotivation in vocabulary mastery,2) tofind outthe interaction between theuse of theapplications(flashcard and scrabble)and the level of the studentsmotivation. This quantitative study was conductedatSMA Negeri 1 Jelimpofrom21st- 28thJanuary2018. The population in this study was the tenth gradersinvolving thestudents of class X MIA asanexperimental class and class X IIS A as a control class. Data collection techniques usedtests,questionnaires,andobservations.The dataanalysisuseda two-wayANOVA.The results show that: (1) There is adifferentmotivation in Vocabulary Mastery inprovingwithanaverage result of 67,7% inthemedium category (2) Media influence to Value (sig = 0,047 <0, 05), while motivation does not affect the value (sig = 0.424> 0.05).(3)This study also findsa difference of effectiveness between the application offlashcardsand scrabble media with the mean of experimental class gains 82,17 and mean of control class gains 68,80.Moreover, the result of observation shows the students of class X MIAare activeand X IIS A are ranged intoa very active, active, and quite active.